2018
DOI: 10.33736/jcshd.787.2018
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Stress Level and Coping Strategies among Undergraduate Students

Abstract: Feelings of stress are a part of university students’ life.  Stress is simply the body's response to changes that create taxing demands. There is a difference between eustress, which is a term for positive stress, and distress, which refers to negative stress. Coping mechanism plays a significant part to overcome or reduce the stress experienced by individuals. People use different types of coping strategies to overcome their stress. The purpose of the study was to study the relationship between stress and cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 18 publications
(16 reference statements)
1
12
0
1
Order By: Relevance
“…Research has shown that students experience stressors such as academic-related stressors, health-related stressors and psychosocial-related stressors in the course of their academic pursuit (Ganesan, Talwar, Norsiah, & Oon, 2018;Okoro, 2018). Most of the studies indicate that distance education students experience diverse stressors and utilise different coping strategies as opposed to regular students (Gyambrah et al, 2017;Kumi-Yeboah, 2010;Kwaah & Essilfie, 2017;Panchabakesan, 2011;Ramos, 2011).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that students experience stressors such as academic-related stressors, health-related stressors and psychosocial-related stressors in the course of their academic pursuit (Ganesan, Talwar, Norsiah, & Oon, 2018;Okoro, 2018). Most of the studies indicate that distance education students experience diverse stressors and utilise different coping strategies as opposed to regular students (Gyambrah et al, 2017;Kumi-Yeboah, 2010;Kwaah & Essilfie, 2017;Panchabakesan, 2011;Ramos, 2011).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Most of the studies indicate that distance education students experience diverse stressors and utilise different coping strategies as opposed to regular students (Gyambrah et al, 2017;Kumi-Yeboah, 2010;Kwaah & Essilfie, 2017;Panchabakesan, 2011;Ramos, 2011). Similarly, majority of research was also conducted on the coping stratagems adopted by these students to manage stress (Ganesan et al, 2018;Govender et al, 2015;Mathew, 2017;Okoro, 2018). Additionally, a few studies on stressors and coping techniques adopted by residential and non-residential college students suggest that residential students face more stress than non-residential students (Kabir et al, 2018;Parveen, 2016), although Addai (2015) found otherwise.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this, there are two constructs that can help individual in dealing with their academic stress and psychological distress which are coping and self-efficacy (Anand & Devi, 2012;Ganesan, Talwar, Fauzan, & Oon, 2018;Moeini et al, 2008). The coping approach an individual use is correlated with psychological distress either positively or negatively (Mahmoud, Staten, Hall, & Lennie, 2012;Park & Adler, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, failure to cope with stress might have an adverse influence on students' mental and physical well-being 4,5 and could become a burden. 6 Yusoff et al 7 conducted a study to determine the impact of medical education on the psychological health of students. The results showed that the main health problems were anxiety (41.1-56.7%), followed by depression (12-30%) and stress (11.9-19.9%).…”
Section: Introductionmentioning
confidence: 99%